Copolymerization of Aniline/Acrylonitrile Using Various Oxidants and Solutions - Ghobadi Bistouni, Bahareh; Eisazadeh, Hossein (Asian Journal of Chemistry, 2010)
An inverted emulsion process was adopted to synthesize conducting copolymer of aniline and acrylonitrile using potassium persulfate, potassium dichromate and benzoyl peroxide as oxidizing agent in different solutions. The chemical structure and morphology of products were characterized by using fourier transform infrared spectroscopy and scanning electron microscope. The results indicate that the morphology, conductivity, homogeneity and particle size are dependent on the type of solution and oxidant. The intensity of peaks related to the type of solution and oxidant.